BEAUTY ADVISOR PERFORMANCE APPRAISAL AT MARTHA TILAAR GROUP JEMBER BRANCH USING CPI METHOD - Ramadhani, Laila Amanda; Nilogiri, Agung; Zakiyyah, Amalina Maryam (Yayasan Nuraini Ibrahim Mandiri, 2024)
Beauty Advisor performance assessment is essential in the beauty industry, maintaining high service standards and increasing customer satisfaction. The researchers developed a decision support system in this study to assess the Beauty Advisor's optimal performance. The system utilized multiple criteria with varying weights for each evaluation. The Composite Performance Index (CPI) is a method used to assess assessments with several stages, greatly influenced by the weights given. The CPI method's calculation process has several stages, including matrix calculation, score matrix calculation, and ranking determination. The final results on the website display a ranking from highest to lowest. The system created based on the success rate with manual calculation results compared to the system calculation results has an accuracy rate of 82%.